2009
DOI: 10.1128/mcb.01389-08
|View full text |Cite
|
Sign up to set email alerts
|

Hnf1α (MODY3) Controls Tissue-Specific Transcriptional Programs and Exerts Opposed Effects on Cell Growth in Pancreatic Islets and Liver

Abstract: Heterozygous HNF1A mutations cause pancreatic-islet ␤-cell dysfunction and monogenic diabetes (MODY3). Hnf1␣ is known to regulate numerous hepatic genes, yet knowledge of its function in pancreatic islets is more limited. We now show that Hnf1a deficiency in mice leads to highly tissue-specific changes in the expression of genes involved in key functions of both islets and liver. To gain insights into the mechanisms of tissue-specific Hnf1␣ regulation, we integrated expression studies of Hnf1a-deficient mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
140
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(162 citation statements)
references
References 80 publications
(124 reference statements)
18
140
0
4
Order By: Relevance
“…by guest, on May 10, 2018 www.jlr.org Downloaded from 20-fold ( 30 ). These studies pointed to the possibility that, like some other HNF1 ␣ target genes, the in vivo regulation of PCSK9 may exhibit redundancy in the ability of HNF1 ␤ to complement absence of HNF1 ␣ .…”
Section: Hepatic Hnf1 ␤ Knockdown Increased Serum Pcsk9 Levels In Micementioning
confidence: 84%
See 2 more Smart Citations
“…by guest, on May 10, 2018 www.jlr.org Downloaded from 20-fold ( 30 ). These studies pointed to the possibility that, like some other HNF1 ␣ target genes, the in vivo regulation of PCSK9 may exhibit redundancy in the ability of HNF1 ␤ to complement absence of HNF1 ␣ .…”
Section: Hepatic Hnf1 ␤ Knockdown Increased Serum Pcsk9 Levels In Micementioning
confidence: 84%
“…Although HNF1 ␤ is expressed at very low levels in adult hepatocytes, a recent report implicated that its expression is induced in HNF1 ␣ Ϫ / Ϫ livers ( 30 ). In vivo binding studies further indicated that loss of HNF1 ␣ triggers signifi cantly higher HNF1 ␤ binding at several HNF1 ␣ target loci, including the PCSK9 promoter region ( 30 ).…”
Section: Cell Culture and Transfectionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, their binding partner PCBD1 might have different effects on the pancreas at different time points. Finally, PCBD1 mutations probably cause HPA and diabetes by affecting not one particular pathway but several genetic, metabolic, and signaling programs in different tissues, as shown for HNF1A gene (24). Future studies will aim to fully understand how PCBD1 regulates b-cell functions and the mechanisms leading to diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these transcription factors regulate complex transcriptional programmes of gene expression by acting on pancreatic cell specific target gene networks [15,16]. Furthermore, in combination with other transcription factors present in mature cells, they interact co-ordinately on the insulin gene promoter to regulate insulin gene expression [4,17].…”
Section: Introductionmentioning
confidence: 99%